The effects of the menstrual cycle on the physiological responses to exercise in eumenorrheic women at high-altitude - Guia Tagliapietra; Tom Citherlet; Antoine Raberin; Giorgio Manferdelli; Bastien Krumm; Benjamin J. Narang; Nicolas Bourdillon; Tadej Debevec; Guido Giardini; Grégoire Millet (Current Issues in Sport Science, 2024)
Introduction